2017
DOI: 10.1038/s41467-017-01944-z
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral perinatal obesogen exposure results in a transgenerational thrifty phenotype in mice

Abstract: Ancestral environmental exposures to non-mutagenic agents can exert effects in unexposed descendants. This transgenerational inheritance has significant implications for understanding disease etiology. Here we show that exposure of F0 mice to the obesogen tributyltin (TBT) throughout pregnancy and lactation predisposes unexposed F4 male descendants to obesity when dietary fat is increased. Analyses of body fat, plasma hormone levels, and visceral white adipose tissue DNA methylome and transcriptome collectivel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
201
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(223 citation statements)
references
References 69 publications
22
201
0
Order By: Relevance
“…Obesogens can also act indirectly to increase fat mass by changing basal metabolic rate, by modulating food intake via effects on the brain, pancreas, adipose tissue, liver, gastrointestinal tract, brain and muscle, by shifting energy balance to favour calorie storage, and by altering the composition of the microbiome [reviewed in]. Recent studies have established that obesogens can alter metabolic “set points” leading to obesity later in life, particularly when dietary composition or caloric intake is changed . Obesogens do not necessarily induce obesity alone, but they can alter developmental programming, affecting nuclear factors or other endocrine pathways during development in ways that lead to obesity later in life.…”
Section: The Obesogen Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Obesogens can also act indirectly to increase fat mass by changing basal metabolic rate, by modulating food intake via effects on the brain, pancreas, adipose tissue, liver, gastrointestinal tract, brain and muscle, by shifting energy balance to favour calorie storage, and by altering the composition of the microbiome [reviewed in]. Recent studies have established that obesogens can alter metabolic “set points” leading to obesity later in life, particularly when dietary composition or caloric intake is changed . Obesogens do not necessarily induce obesity alone, but they can alter developmental programming, affecting nuclear factors or other endocrine pathways during development in ways that lead to obesity later in life.…”
Section: The Obesogen Hypothesismentioning
confidence: 99%
“…Prenatal nicotine exposure in rats produced adults that required less high‐fat food to gain weight . Exposure of F0 female mice to TBT throughout pregnancy and lactation led to males of the unexposed F4 generation gaining weight very rapidly when dietary fat was increased; they retained much of this extra fat even after their chow was returned to the previous low‐fat diet . The animals also overexpressed leptin, and the authors inferred they were leptin‐resistant .…”
Section: Can Obesogens Modulate Metabolic Set Points?mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects led to a more significant decline in basal metabolic rate during weight loss and less increase in basal metabolic rate during weight regain. Chamorro‐Garcia et al showed that ancestral exposure to tributyltin resulted in animals (four generations later) that were more sensitive to gaining weight when they were switched to a high‐fat diet compared to control animals. When these animals were returned to a standard control diet, they lost weight more slowly than control animals.…”
Section: Obesogensmentioning
confidence: 99%
“…Experimental studies in non‐mammalian systems are providing crucial mechanistic insight . Thus, a recent study, presented at PPTOX VI, showed that transgenerational inheritance of obesity was observed from perinatal tributyltin exposure, apparently mediated through altered higher‐order chromatin organization . Reorganized chromatin, transmissible through meiosis and mitosis, can in turn influence DNA methylation at accessible sites that modified transcription, suggesting that this is a proximal event.…”
Section: Mechanistic Insightsmentioning
confidence: 99%